Glabridin Attenuates the Retinal Degeneration Induced by Sodium Iodate In Vitro and In Vivo - Aung, Kaung Htet; Liu, Hua; Ke, Zongwen; Jiang, Shuang; Huang, Jianhua (Frontiers in Pharmacology, 2020)
BACKGROUND: Age-related macular degeneration(AMD), one of the major causes of blindness in the elderly over age of 60, is divided into dry AMD and wet AMD. Although there are certain treatment methods for wet Age-related macular degeneration(AMD), there is no effective treatments for dry AMD yet. Hence, finding new drugs or treatment methods for dry AMD has become a priority. The effect of Glabridin(Glab), an isoflavane found in the root extract of licorice, has never been investigated in any eye diseases. PURPOSE: To investigate the effect of Glab on the sodium iodate(SI) induced retinal degeneration in vitro and in vivo. METHODS: In vitro, cell viability and cytotoxicity were tested with methylthiazolyldiphenyl‐tetrazolium bromide(MTT) assay among the groups of ARPE-19 cells. The cell apoptosis was tested with Hoechst 33342 staining and flow cytometry. The level of Reactive oxygen species(ROS) was measured to check the effect on the oxidative stress. The protein expressions of phosphorylation of ERK1/2 and p38 were detected by Western blotting. In vivo, C57BL / 6J mice were pretreated with Glab intraperitoneally for one week and continued for 4 weeks. SI was given to mice through tail vein intravenous injection after 1 week of Glab administration. The retinas of mice were monitored by Optical coherence tomography(OCT) and electroretinography(ERG) at 1w, 2w, 3w and 4w respectively following with H&E staining. RESULTS: In vitro, Glab protected the retinal pigment epithelial(RPE) cells against oxidative stress and apoptosis by inhibiting phosphorylation of ERK1/2 and p38 MAPK pathway. In vivo, Glab significantly prevented the retinal damage by stopping the progression of retinal degeneration and reducing formation of deposits on RPE layer induced by SI. According to electroretinogram(ERG) findings, Glab maintained the normal function of retina. CONCLUSION: Glabridin has the protective effect against retinal degeneration and it is suggested to be further investigated for the treatment of retinal degeneration diseases.